Enzyme and hormone activities related to phosphorus uptake limitation in oil palm (Elaeis guineensis Jacq.) - Maryanto, Sigit Dwi; Rohman, Randi Abdur; Roberdi, Roberdi; Nuringtyas, Tri Rini; Purnomo, Purnomo; Rachmawati, Diah; Putra, Eka Tarwaca Susila; Utomo, Condro; Liwang, Tony; Daryono, Budi Setiadi (Universitas Gadjah Mada, 2025)
Phosphorus (P) is an essential element for oil palm growth and development. Acid phosphatase (Apase) and Pti‐interacting serine/threonine kinase are two enzymes which enzymes confirmed to be related to P‐uptake in oil palm, therefore their activities in oil palm treated with P‐limitation need to be quantified. Acid phosphatase is believed to be induced by P‐deprivation. Conversely, the Pto‐interaction (Pti) serine/threonine kinase activity is associated with abiotic stress. The aim of this study was to quantify of activities of two selected enzymes and phytohormone content in oil palm‐clones in the P‐limitation condition. Two oil palms genotypes were treated with three P dosages i.e. 0% (v/v), 4.67% (v/v), and 14.02% (v/v) represented as starvation, deficiency, and optimum condition, respectively. The activity of these two enzymes was quantified in mitochondria and cytoplasm using spectrophotometry and modified dot‐blot methods, while abscisic acid, indole acetic acid and gibberellic acid content was quantified using ultra performance liquid chromatography (UPLC). The result showed that the Apase activity in P‐optimum was higher than starvation and deficiency in leaf and root tissues in both genotypes, whereas Pti serine/threonine kinase activity was higher in prolific than non‐prolific genotypes in P‐deficient dosage. Furthermore, abscisic acid content was higher in prolific than non‐prolific genotypes in starvation and deficient, whereas other hormone contents were similar. Association study showed that prolific was separated with non‐prolific ones at different doses of P. Finally, the prolific genotype is more adaptable with P deficiency.